1-Methyl-8-phenyl-1,3-diazaspiro[4.5]decane-2,4-dione - Vasiliki Pardali (Molbank, 2021)
A simple, fast and cost-effective three-step synthesis of 1-methyl-8-phenyl-1,3-diazaspiro[4.5]decane-2,4-dione has been developed. The reactions described herein proceed readily, with high yields and no further purification. Therefore, the proposed method, with an overall yield of 60%, offers a facile pathway to the synthesis of N-1 monosubstituted spiro carbocyclic imidazolidine-2,4-diones (hydantoins), which constitute a privileged class of heterocyclic scaffolds with pharmacological interest.